The Blue Carbon Explorer: a Google Earth Engine tool for mangrove restoration - McNulty, Valerie Pietsch; Perez, Denise; Simpson, Stefanie; Beneby, Jewel; Joseph-Witzig, Andre; Jones, Loúreene; Smart, Lindsey; Moyer, Ryan P.; Gibson, Solomon; Musgrove, Marcia; Cattafesta, Catherin; Schill, Steven R. (Frontiers in Environmental Science, 2025)
The Insular Caribbean is home to over half a million hectares of mangroves, blue carbon ecosystems that can store up to 5 times as much carbon as upland forests while also protecting coastal communities, supporting fisheries, and fostering marine biodiversity. The Blue Carbon Explorer, a Google Earth Engine app, was launched in 2023 to identify areas for mangrove protection and restoration. The tool allows users to visualize and inspect changes in the Normalized Difference Vegetation Index (NDVI) of mangrove habitats over various temporal and spatial scales using Norway’s International Climate & Forests Initiative PlanetScope mosaics (Planet-NICFI), Sentinel-2 images, and Landsat archive composites, as a proxy for habitat condition, indicative of active photosynthesis. Users can also explore lidar and radar-derived canopy height data, analyze changes in mangrove area and extent using the Mangrove Vegetation Index (MVI), calculate areas of significant change based on NDVI, and prioritize mangrove areas for restoration based on their likelihood to recover naturally. Previous mangrove restoration efforts in the Caribbean have largely been based on enhancing coastal protection benefits, as a Nature-based Solution (NbS) for climate adaptation. The Blue Carbon Explorer (BCE) provides governments and conservation practitioners with an easy-to-use decision support tool for tracking changes in mangroves and identifying priority areas for conservation and restoration aimed at ecological recovery and enhancing carbon storage. As proof of concept, we demonstrate the use of the BCE to track mangrove change in Grenada, Jamaica, the Dominican Republic, and The Bahamas. In The Bahamas, highly detailed canopy height data was used to develop a novel prioritization analysis that informed a mangrove restoration plan following Hurricane Dorian.